2011
DOI: 10.1016/j.jmpt.2010.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bending Stiffness and Lumbar Spine Range of Movement Following Lumbar Mobilization and Manipulation

Abstract: Manipulation and mobilization had no significant effect on bending stiffness or flexion and extension ROM for this group of subjects. Some individual variations in effect were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 32 publications
0
28
1
5
Order By: Relevance
“…These results are in contrast to Petty [65] , Chiradejnant et al [66 -67] and Stamos-Papastamos et al, [32] who all found no significant effect of lumbar mobilisations on range of motion. However, both Powers et al [68] and McCollam and Benson [69] both have reported increases in ROM post mobilisation.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…These results are in contrast to Petty [65] , Chiradejnant et al [66 -67] and Stamos-Papastamos et al, [32] who all found no significant effect of lumbar mobilisations on range of motion. However, both Powers et al [68] and McCollam and Benson [69] both have reported increases in ROM post mobilisation.…”
Section: Discussioncontrasting
confidence: 74%
“…Grade three mobilisations were applied to the intervention group by a physiotherapist with 9 years' clinical experience and postgraduate manual therapy qualifications. The mobilisation was performed for two minutes, three times alternating between L4 and L5, without rest in between [28,32] . Each vertebra level was determined by the palpation of relevant spinous processes and passive physiological intervertebral movement.…”
Section: Lumbar Mobilisationsmentioning
confidence: 99%
“…Several other studies have measured stiffness in the thoracic or lumbar spine immediately following the application of various manual techniques and reported no significant changes, 1,7,21,61 though only 1 of these 21 was in symptomatic patients. This suggests that the mechanism of action of manual therapy may not be mechanical in nature but, instead, may be related to the presence of pain, as the current study found that the group that demonstrated decreased stiffness at follow-up was also the group that reported less pain.…”
Section: Spinal Stiffnessmentioning
confidence: 95%
“…[9][10][11][12][13] Therefore, a variety of technologies have been developed and applied in the attempt to quantify biomechanical characteristics. [14][15][16] Some technologies have been designed to investigate the motion of each vertebra (segmental motion), that is, digitized videofluoroscopic images 17 or by invasive methods, 12,18 and others are designed to measure the spine on a regional level, for example, in the entire lumbar spine. 19,20 Noninvasive, real-time 3-dimensional (3D) regional instruments can provide a quantitative assessment of complex spinal kinematics (eg, coupled motion, combined motion, velocity, acceleration, and smoothness of motion [jerk index]).…”
mentioning
confidence: 99%